Is Rural Enterprise God's Business?. (2nd July 2016) - Marshall, Jerry
Abstract : Enterprise and entrepreneurship are sometimes viewed with suspicion by church leaders and may not be seen as relevant to the rural church. Drawing on biblical understanding and personal experience as a 'kingdom entrepreneur', this paper argues that enterprise is part of scripture, human flourishing, and mission. The paper contends that enterprise is especially important in rural areas and faith centred enterprise can be traced back to Cistercian monasteries and continues today. The mission of the rural church would be enriched by recognising, encouraging and harnessing entrepreneurs, and supporting enterprise creation. The paper is commented upon by two further authors who reflect upon its approach to theology and entrepreneurship.